2015
DOI: 10.1007/s00262-015-1726-0
|View full text |Cite
|
Sign up to set email alerts
|

Immune biomarkers are more accurate in prediction of survival in ulcerated than in non-ulcerated primary melanomas

Abstract: Introduction Ulcerated melanomas may have a unique biology and microenvironment. We test whether markers of immune infiltration correlate with clinical outcome in ulcerated compared to non-ulcerated primary melanoma tumors. Methods Sixty-two stage II–III cutaneous melanomas, 32 ulcerated and 30 non-ulcerated, were analyzed for tumor-infiltrating lymphocytes (TILs). Immunohistochemistry (IHC) was performed for CD2, a marker previously shown to correlate with overall survival (OS) and recurrence-free survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 39 publications
(52 reference statements)
1
25
0
Order By: Relevance
“…So far, most groups studying the correlation between TILs and patient survival classify the presence of TILs as absent, nonbrisk and brisk (11,15,16). Some characterize TILs only as present or absent (44), while few use a more elaborate method that takes both the distribution and the density of TILs into account (12). Our method also takes distribution and density into account and does this in an automated and quantitative manner using the entire tumor slide.…”
Section: Discussionmentioning
confidence: 99%
“…So far, most groups studying the correlation between TILs and patient survival classify the presence of TILs as absent, nonbrisk and brisk (11,15,16). Some characterize TILs only as present or absent (44), while few use a more elaborate method that takes both the distribution and the density of TILs into account (12). Our method also takes distribution and density into account and does this in an automated and quantitative manner using the entire tumor slide.…”
Section: Discussionmentioning
confidence: 99%
“…Since both NM and ALM are associated with lower levels of tumor infiltrating lymphocytes, which are known to correlate with poor outcomes in melanoma, it is possible that differences in the immunogenicity of the primary melanoma are relevant for recurrence after negative SLNB [13,14]. Similarly, changes in the tumor microenvironment in ulcerated melanoma might explain why ulceration is associated with overall recurrence in patients with negative SLNs, since ulcerated melanoma may interact differently with the immune system [15]. To our knowledge, our study is the first to identify ulceration as a risk factor for hematogenous spread.…”
mentioning
confidence: 99%
“…This is reinforced by the effectiveness of immunotherapies based on immune checkpoint blockers that allow for reversal of melanoma-induced immunosuppression correlated with the presence of neoantigens expressed by the tumor (McGranahan et al, 2016;Van Allen et al, 2015). Consistent with this hypothesis, some studies suggested that the presence, number, or quality of T lymphocyte infiltrates, specifically CD8 + T cells, is an independent and favorable prognostic factor in melanoma (Erdag et al, 2012;Jacquelot et al, 2016;de Moll et al, 2015;Piras et al, 2005). Ongoing investigations are analyzing the host immune response against cancer to evaluate the prognostic impact of in situ immune-cell infiltrates in tumors and defined as an "immunoscore" (Galon et al, 2012).…”
Section: Discussionmentioning
confidence: 91%